Thermal Characteristic of Novel Insulation Materials Designed for Solar Simulator - Ding, Wenjing; Zhou, Ying; Gu, Miao; Gong, Jie; Xu, Jinghao (Energies (Basel), 2022)
The solar simulator is an important device for simulating solar irradiation in cold black and vacuum environments and has a wide range of application prospects. In this work, a method of thermal conductivity measurement by a double specimen protection thermal plate method under vacuum conditions was proposed, and the thermal conductivity of a new thermal insulation material under a cryogenic vacuum environment was studied. By designing a vacuum adjustment device and a multi-layer insulation structure with a low outgassing rate, it is possible to adjust the vacuum pressure from 10−4 Pa to atmospheric. A temperature control and thermal conductivity test can be realized from −160 °C to 280 °C by the joint temperature control of liquid nitrogen cooling and electric heating. Then, the measurement accuracy of the device was checked by the national standard sample, the thermal conductivity of the sample was measured under different vacuum and temperature conditions, the uncertainty analysis of the device was given, and, finally, the thermal conductivity of the new material was tested.